THE USE OF HORMONES DURING THE PERIMENOPAUSAL PERIOD IN SLOVENIA - Damir Franić; Jurij Fürst (Zdravniški Vestnik, 2003)
Background. We want to collect data on the use of hormone therapy (HT) in perimenopausal women in Slovenia. These data were to serve as the basis for evaluation of the most frequently prescribed HT, and of the distribution of prescriptions by Slovene health regions. Consequently, the percent of women aged 40–65 years, current hormone replacement therapy (HRT) users was to be assessed. Methods. The analysis was made on the basis of the data collected by the automatic processing of prescriptions (AOR). Reliability of the data has been excellent since the introduction of the health insurance card. The data on drug use are expressed as defined daily doses (DDD) per 1000 inhabitants aged 40–65 years. The information on the number of women in a certain age group and their number in a certain medical region was obtained from the Statistical Institute of Slovenia and from the database of the Institute of Health Insurance of Slovenia. DDD is a technical unit, by means of which drug use can be compared. DDD is a mean daily dose of the drug prescribed for the main indication in adults, the unit being 1 gram of the active substance. The AOR data have become reliable after 2001, therefore our analysis comparised the years 2001 and 2002. Comparison of the data was done using the list of drugs prepared according to the Anatomical Therapeutic Chemical classification (ATC) for coding drugs. Results.  HRT (at least one pack) was found to be used by 12.5% of women in 2001 and 12.4% in 2002. The estimated percent of women receiving HRT for at least 6 months was 6.5% in 2001 and 6.4% in 2002. Considering DDD, most frequently prescribed drugs were estrogens and monophasic estrogens + progesterone, these in the age groups 45–55 years; beyond this age HT was used decreasingly. Conjugated equine estrogen and antiandrogens combined with estrogens were prescribed the least. By medical regions, most systemic hormones were prescribed in the Ljubljana and Novo mesto regions, and least in the Murska Sobota and Krško regions. Local estrogens were most frequently prescribed in the Murska Sobota, Nova Gorica and Koper regions, and least frequently in the Krško region. The HRT prescription rate showed a 5–19% decrease in 2002 compared to 2001. Conclusions. Although by the prescribed DDD of HRT Slovenia is comparable to Denmark, HT is not being used continuously by sufficient percent of women (6.5%). Therefore it is mandatory, especially for stricter indications for HRT, to provide better education to professionals, who are to properly advise Slovene women on how and when to decide on HRT use.